NanoSTAIR: a new strategic proposal to impulse standardization in nanotechnology research. (May 2015) - de Ipiña, J M López; Salvi, O; Hazebrouck, B; Jovanovic, A; Carre, F; Saamanen, A; Brouwer, D; Schmitt, M; Martin, S
Abstract: Nanotechnology is considered one of the key technologies of the 21 st century within Europe and a Key-Enabling Technology (KET) by Horizon 2020. Standardization has been identified in H2020 as one of the innovation-support measures by bridging the gap between research and the market, and helping the fast and easy transfer of research results to the European and international market. The development of new and improved standards requires high quality technical information, creating a fundamental interdependency between the standardization and research communities. In the frame of project nanoSTAIR (GA 319092), the present paper describes the European scenario on research and standardization in nanotechnology and presents a proposal of a European strategy (nanoSTAIR) to impulse direct "pipelines" between research and standardization. In addition, strategic actions focused on integration of standardization in the R&D projects, from the early stages of the design of a future business (Project Proposal), are also described.